Tears of history: the rise of political antisemitism in the United States - Birnbaum, Pierre (European perspectives a series in social thought and cultural criticism, 2023)
"Salo Baron was born in 1895 under the Habsburg empire and became one of the greatest historians of Judaism. He testified at the Eichmann trial. Baron was invited to teach in New York in 1926. When he got here he discovered what he thought was the American exception: as a new society, the United States would have not experienced any persecutions of Jews. That would alone refute--in his own words--"a lachrymose version of history," the story that lays out the destiny of Judaism as an uninterrupted list of persecutions and massacres. At most, he thought, American Jews would meet with prejudice or social barriers, but never antisemitism theorized as a political ideology. And yet, in 1913, in Atlanta, there was the case of Leo Frank: the lynching of a Jew accused of the ritual murder of a young woman, even though the charges had been dropped. It was the first American instance of hate-driven antisemitism. Some years later, Roosevelt's New Deal radically transformed the destiny of American Jews. For the first time powerful figures such as Henry Morgenthau and Louis Brandeis came to the fore, and Jews experienced a newfound prominence. Antisemites in America declared that Jews, having taken over the government, would destroy America's identity. During the period from Roosevelt to Obama, antisemitism increased and was clearly seen recently in the neo-Nazi march in Charlottesville in 2017 and in the Tree of Life Synagogue mass shooting in Pittsburgh in 2018. Antisemitic violence continues to grow here. On January 6, 2021, the attempted coup against the Capitol saw an outpouring of violently antisemitic slogans. All of which begs the question: does this mean that the romantic view of American exceptionalism, sanctified by many historians of American Judaism, has been refuted once and for all? Is the idea of this place of exile, seen as a protective and exceptional "home," in fact an illusion? Should it also be considered as the return of a "lachrymose" history? This book seeks to explore the answers to these questions"